The exemplary PDS partnership award: an overview and review of publications from award recipients - Drew Polly (PDS Partners)
Purpose – The National Association for School-University Partnerships ([NASUP], formerly known as the National Association for Professional Development Schools [NAPDS]), annually awards the Exemplary PDS Partnership Award to partnerships who exemplify many or all of the NAPDS Nine Essentials (NAPDS, 2021). This article provides an overview of the Exemplary PDS Award and provides a review of peer-reviewed journal articles published by recipients of the NASUP/NAPDS Exemplary PDS Partnership Award between 2014 and 2024. Design/methodology/approach – This paper uses a basic review of literature. Findings – Findings indicate that most Exemplary PDS Awards between 2014 and 2024 cite the NAPDS Essentials 1 and 4. Essential 1 focuses on PDS partnerships have a comprehensive mission and mutually beneficial partnership that advances teaching, learning, and equity. Essential 4 focuses on innovative practice and reflecting on PDS partnership activities. Originality/value – This article provides a review of peer-reviewed journal articles published by recipients of the Exemplary PDS Award.